In-silico and in-vitro assessments of some fabaceae, rhamnaceae, apocynaceae, and anacardiaceae species against Mycobacterium tuberculosis H37Rv and triple-negative breast cancer cells - Kudakwashe Nyambo; Francis Adu-Amankwaah; Kudzanai Ian Tapfuma; Lucinda Baatjies; Lauren Julius; Liezel Smith; Mkhuseli Ngxande; Krishna Govender; Lawrence Mabasa; Afsatou Traore; Maano Valerie Masiphephethu; Idah Sithole Niang; et al. (BMC, 2023)
Abstract Medicinal plants play a huge role in the treatment of various diseases in the Limpopo province (South Africa). Traditionally, concoctions used for treating tuberculosis and cancer are sometimes prepared from plant parts naturally occurring in the region, these include (but not limited to) Schotia brachypetala, Rauvolfia caffra, Schinus molle, Ziziphus mucronate, and Senna petersiana. In this study, the aim was to evaluate the potential antimycobacterial activity of the five medicinal plants against Mycobacterium smegmatis mc2155, Mycobacterium aurum A + , and Mycobacterium tuberculosis H37Rv, and cytotoxic activity against MDA-MB 231 triple-negative breast cancer cells. Phytochemical constituents present in R. caffra and S. molle were tentatively identified by LC-QTOF-MS/MS as these extracts showed antimycobacterial and cytotoxic activity. A rigorous Virtual Screening Workflow (VSW) of the tentatively identified phytocompounds was then employed to identify potential inhibitor/s of M. tuberculosis pantothenate kinase (PanK). Molecular dynamics simulations and post-MM-GBSA free energy calculations were used to determine the potential mode of action and selectivity of selected phytocompounds. The results showed that plant crude extracts generally exhibited poor antimycobacterial activity, except for R. caffra and S. molle which exhibited average efficacy against M. tuberculosis H37Rv with minimum inhibitory concentrations between 0.25-0.125 mg/mL. Only one compound with a favourable ADME profile, namely, norajmaline was returned from the VSW. Norajmaline exhibited a docking score of -7.47 kcal/mol, while, pre-MM-GBSA calculation revealed binding free energy to be -37.64 kcal/mol. All plant extracts exhibited a 50% inhibitory concentration (IC50) of < 30 μg/mL against MDA-MB 231 cells. Flow cytometry analysis of treated MDA-MB 231 cells showed that the dichloromethane extracts from S. petersiana, Z. mucronate, and ethyl acetate extracts from R. caffra and S. molle induced higher levels of apoptosis than cisplatin. It was concluded that norajmaline could emerge as a potential antimycobacterial lead compound. Validation of the antimycobacterial activity of norajmaline will need to be performed in vitro and in vivo before chemical modifications to enhance potency and efficacy are done. S. petersiana, Z. mucronate, R.caffra and S. molle possess strong potential as key contributors in developing new and effective treatments for triple-negative breast cancer in light of the urgent requirement for innovative therapeutic solutions.